2015
DOI: 10.1155/2015/390416
|View full text |Cite
|
Sign up to set email alerts
|

Ninety-Day Oral Toxicity Assessment of an Alternative Biopolymer for Controlled Release Drug Delivery Systems Obtained from Cassava Starch Acetate

Abstract: The large consumption of biodegradable films from cassava starch acetate (FCSA) as ingredients in food and pharmaceutical products requires the assessment of the possible toxicity of these products. The aim of this study was to investigate the toxicity of biodegradable film from cassava starch acetate after oral exposure of Wistar rats for 90 days. The amount of food consumed and the body weight were weekly monitored. Blood and urine samples were obtained for the assessment of serum parameters and renal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In a research investigation, 90 days acute oral toxicity assessments of biodegradable lm from acetate cassava starch were investigated in Wister rats (dose range 3, 30, and 300 mg/kg body weight) and results revealed that cassava starch acetate (300 mg/kg body weight) does not cause obvious sign of toxicity as well as relative organ weight and histopathological evaluations did not show much difference in comparison to control group (water), which further indicates the safety of this acetate cassava starch based bio lms. However, further studies in this area are very essential for the exploration of suitable safety e cacy of modi ed cassava starch [192].…”
Section: Subchronic Toxicitymentioning
confidence: 99%
“…In a research investigation, 90 days acute oral toxicity assessments of biodegradable lm from acetate cassava starch were investigated in Wister rats (dose range 3, 30, and 300 mg/kg body weight) and results revealed that cassava starch acetate (300 mg/kg body weight) does not cause obvious sign of toxicity as well as relative organ weight and histopathological evaluations did not show much difference in comparison to control group (water), which further indicates the safety of this acetate cassava starch based bio lms. However, further studies in this area are very essential for the exploration of suitable safety e cacy of modi ed cassava starch [192].…”
Section: Subchronic Toxicitymentioning
confidence: 99%
“…The toxicity study reveals that no acute adverse reactions like convulsions, salivation, lethargy, diarrhea in the albino mice during the entire observation period. Therefore, it was assumed that thiolated starch was easily digested by the animals by avoiding any kind of toxic effects [58].…”
Section: Acute Toxicity Studymentioning
confidence: 99%
“…Its abundant, cheap, nontoxic, and renewable potential as a substitute for non-biodegradable synthetic polymers. 1114 However, starch shows low mechanical properties and high hygroscopicity, which can be improved by developing multiphase systems, such as the biocomposites. 15,16…”
Section: Introductionmentioning
confidence: 99%